Evaluation of Galectin-3 and Myocardial Fibrosis in Patients with Hypertrophic Cardiomyopathy - Antunes,Murillo de Oliveira (2019)
Abstract Background: Galectin-3 is the designation given to the protein that binds to ß-galactosides, expressed by activated macrophages and described as a cardiac fibrosis mediator. In hypertrophic cardiomyopathy (HCM), myocardial fibrosis is an independent predictor of adverse outcome; however, the association between Galectin-3 and myocardial fibrosis has not been studied in this cardiopathy. Objective: To evaluate the association of Galectin-3 and the presence of myocardial fibrosis in a patient with hypertrophic cardiomyopathy. Methods: Galectin-3 was measured in automated equipment using the Elisa technique in 100 participants divided into two groups: 50 patients with hypertrophic cardiomyopathy and 50 healthy control subjects. All patients with hypertrophic cardiomyopathy underwent magnetic nuclear resonance with the late enhancement technique to investigate myocardial fibrosis. For the statistical analysis, p values < 0.05 were considered statistically significant. Results: Galectin-3 levels were low and did not show significant differences between patients with hypertrophic cardiomyopathy and the control group, 10.3 ± 3.1 ng/dL and 11.3 ± 2.6 ng/dL (p = 0.12) respectively. Myocardial fibrosis was a common finding and was identified in 84% (42/50) of patients with HCM, but no differences were observed between Galectin-3 levels when comparing patients with and without fibrosis, 10.3 ± 2.4 ng/dL and 10.1 ± 2.1 ng/dL (p = 0.59). Conclusion: The results did not show an association between Galectin-3 and myocardial fibrosis in patients with hypertrophic cardiomyopathy, suggesting that non-inflammatory mechanisms of myocardial fibrosis formation and cardiac remodeling are involved in this cardiopathy.